The making of fornication : eros, ethics, and political reform in Greek philosophy and early Christianity - Gaca, Kathy L. (Joan Palevsky imprint in classical literature., 2003)
This work provides a reassessment of the emergence and nature of Christian sexual morality, the dominant moral paradigm in Western society since late antiquity. It shows that early Christian goals to eradicate fornication were derived from the sexual rules and poetic norms of the Greek bible.